PENGARUH TERAPI BERMAIN ULAR TANGGA TERHADAP KECEMASAN HOSPITALISASI ANAK USIA PRA SEKOLAH 3–6 TAHUN DI RUANG ANAK RSUD PALABUHAN RATU: THE EFFECT OF SNAKES AND LADDERS PLAYING THERAPY ON THE HOSPITALIZATION ANXIETY OF PRESCHOOL AGE CHILDREN 3–6 YEARS IN CHILDREN'S ROOM PALABUHAN RATU HOSPITAL - Hermawati, Ila (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2024)
Hospitalization of preschool-aged children is a condition that requires children to stay in hospital, undergo treatment and care for planned reasons or emergency situations. Hospitalization that is not handled properly can cause persistent anxiety, and if this anxiety is not addressed, it can result in mental health problems. One non-pharmacological therapy to overcome the problem of hospitalization is play therapy. This study aims to determine the effect of snakes and ladders play therapy on the anxiety of hospitalization of pre-school aged children in the children's room at Palabuhan Ratu Regional Hospital. The research method used was a pre-experimental method without a control group and the design of this research was to use only one group with a pretest and posttest. The results of the research showed that 7.8% of respondents experienced mild anxiety before snakes and ladders play therapy and 92.2% experienced moderate anxiety. Anxiety after snakes and ladders play therapy, a small percentage of respondents experienced moderate anxiety of 7.8% and mild anxiety of 92.2%. The results of the Wilcoxon signed ranks test show a significance value of 0.000, smaller than 0.05, so it can be concluded that Ha is accepted, meaning that there is a significant influence between snakes and ladders play therapy intervention before being carried out in reducing anxiety in pre-school children aged 3 - 6 years. It is hoped that the results of the research will increase nurses' knowledge about the importance of play therapy, one of which is playing snakes and ladders as an intervention in providing nursing care to help reduce children's anxiety, especially preschool aged children who are undergoing treatment